Oxidative Oligomerization of Fischer–Tropsch Internal Olefins Catalyzed by Metal Octoates of s, p and d Block Elements - Kataria, Yash Vijay; Lavrenov, Sergey A.; Yakovenko, Evgeniya Yu.; Klushin, Victor А.; Yakovenko, Roman E.; Kashparova, Vera P.; Zubkov, Ivan N. (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
In the present work we further expanded the scope of the study of the oxidative oligomerization process of synthetic hydrocarbon fraction obtained by Fischer–Tropsch synthesis with a total olefin content (consisting predominantly internal/branched olefins) of 10 % with the aim of producing poly-α-olefin like lubricant material. The oxidative oligomerization was carried out using commercially available metal octoates based on Co, Mn, Zn, Ca, Ba, Li, Zr, Cu and Pb and their combinations as catalyst. It was established that the yield of the oligomerization reaction depending on the active metal component used decreased in the following order: Ba > Zr > Zn > Co > Mn > Ca > Li > Cu > Pb. While at the same time, the oxidative oligomerization reaction carried out using bimetallic catalytic systems did not led to any significant increase in the product yield. The oxidative oligomerization reaction using Ba octoate as catalyst gave a yield of 30.4 % and had a kinematic viscosity at 100 °C of 3.6 cSt, Viscosity Index value of 201 and pour point of minus 10. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).